Large Economies with Trading Uncertainty: A Correction - Gale, Douglas (Review of Economic Studies, 1981)
of Mannheim University has brought to my attention an error in my paper "Large Economies with Trading Uncertainty". The example of an allocation mechanism described on pp. 329-332 does not satisfy the condition of relative continuity as claimed on p.332. The reason is that the definition, as given in the paper, is a rather gross misstatement of what I had in mind and makes some of the accompanying analysis nonsensical. Fortunately, the matter is not hard to put right. Two passages in the text must be rewritten as follows.